2012
DOI: 10.1017/s0021859612000779
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of crop models to extreme weather conditions during flowering period demonstrated for maize and winter wheat in Austria

Abstract: SUMMARYThe objective of the present study was to compare the performance of seven different, widely applied crop models in predicting heat and drought stress effects. The study was part of a recent suite of model inter-comparisons initiated at European level and constitutes a component that has been lacking in the analysis of sources of uncertainties in crop models used to study the impacts of climate change. There was a specific focus on the sensitivity of models for winter wheat and maize to extreme weather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 70 publications
3
53
0
1
Order By: Relevance
“…Years with extreme or contrasting weather conditions have recently been used to assess the ability of crop models in simulating yield responses to variability in the weather (Eitzinger et al 2012). The results showed that even a short period of extreme hot weather may cause considerable differences among models.…”
Section: Validation Methodologiesmentioning
confidence: 99%
“…Years with extreme or contrasting weather conditions have recently been used to assess the ability of crop models in simulating yield responses to variability in the weather (Eitzinger et al 2012). The results showed that even a short period of extreme hot weather may cause considerable differences among models.…”
Section: Validation Methodologiesmentioning
confidence: 99%
“…It refers to both a shift in mean climatic conditions (e.g. temperature and precipitation) and an increase in the frequency and severity of weather extremes (Tebaldi et al 2006;Eitzinger et al 2013;Porter et al 2014;Mandryk et al 2017). Economic activities prompted by industrial revolution have been contributed to climate change through increasing GHGs emission (IPCC 2007a).…”
Section: Agriculture and Climate Change: A Two-way Relationshipmentioning
confidence: 99%
“…The effects of adverse weather events on crops and agricultural crop production are still poorly understood and their prediction with crop models is currently very difficult [6,41]. The conclusion of our study, based on the applied DSSAT models, is that the simulated yields show less sensitivity to AWCs, as represented by the selected AMI, than the correlation with actual yields.…”
Section: Discussionmentioning
confidence: 77%
“…Soils 3 and 4 are Chernozems and Fluvisols, respectively, with an available water capacity of >140 mm for a soil depth of 100 cm (sandy loam and loamy silt, respectively). DSSAT was applied at all locations of this study with calibration on Austrian WW and MZ cultivars [41]. All simulations specified a rain-fed water supply, automatic planting, N-fertilizer auto application, and an atmospheric CO2 concentration of 390 ppm, which reflects the mean value for the period of interest.…”
Section: Crop Yield Simulationsmentioning
confidence: 99%
See 1 more Smart Citation